Subnational Purchasing Power Parities toward Integration of International Comparison Program and Consumer Price Index: The Case of the Philippines - Yuri Dikhanov; Chellam Palanyandy; Eileen Capilit (Asian Development Bank (ADB), 2011)
The International Comparison Program (ICP) compares levels of economic activity and relative price levels among countries of the world. The main feature of the ICP is that it produces spatial indexes or purchasing power parities (PPPs) that allow cross-country comparison of gross domestic product (GDP) and its major aggregates. While the PPPs produced from ICP are spatial indexes, the consumer price index (CPI) is temporal and measures the changes in the average prices of a fixed basket of goods and services purchased by households from one period to another. This paper describes how information from the CPI can be used for intracountry comparisons of price levels (spatial comparisons) that would be consistent in the temporal dimension. In this way the output is temporally consistent subnational price levels (subnational PPPs) that can be used in regional price comparisons, real income dimension of human development indexes, poverty estimates, regional cost of living indexes, etc. This study aims to analyze the plausibility of integrating ICP with the Philippines' CPI by computing subnational PPPs using regional prices and expenditure weights from the CPI. This study also aims to find out whether prices collected for the CPI could be used to provide reliable estimates of price levels for a range of products in each region, and show if the relationships between these price levels are consistent with information coming from the ICP process. The current project using data collected from the Philippines' CPI has shown that the subnational price levels obtained from both the CPI and ICP processes are broadly similar. The study shows that all regional price movements are highly correlated, which is probably an indication of efficiency of the markets. However, the substitution effects cannot be studied right now as the only available expenditure structure at the time of subnational PPP estimation is for 2000. Incorporating substitution effects of changing expenditure patterns should improve the estimate.
hdl:11540/1991
Keywords: 330; Kaufkraftparität; Verbraucherpreisindex; Philippinen